no2.3064PENERAPAN OMNIBUS LAW CIPTA KERJA DI INDONESIA EFEKTIF ATAU TIDAK?STUDI TINJAUAN BERDASARKAN SISTEM HUKUM DI INDONESIA - Putri, Dewi Sartika (Jurnal Hukum & Pembangunan, 2021)
The overlapping of regulations in Indonesia makes Indonesian people uneasy in thismatter, business actors in implementing these various regulations. Besides overlapping regulations, the ineffectiveness of these regulations in terms of licensing submission procedures to the minimum supervision by the government has caused disappointmentfor many business actors who apply for licenses in opening their businesses. This can be an obstacle in the investment business climate in Indonesia. Therefore, President Jokowi in his speech at the time he was elected as the second President of Indonesia, alluded to the Omnibus Law on Employment Creation which meant simplifying regulations, especially in the licensing process to facilitate business actorsin opening their businesses in Indonesia.Many support this, especially business actors in Indonesia who want to develop their businesses, but many academics debate the policy of implementing the Omnibus Law whether it will be effective if implemented in Indonesia, given that Indonesia adheres to the civil law legal system.